2012
DOI: 10.1002/j.1532-2149.2012.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive responses to thermal and mechanical stimulations in awake pigs

Abstract: Our data indicate that this experimental approach may be valuable for use in studies that focus on porcine cutaneous nociception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…Di Giminiani et al (2013) have demonstrated that smaller pigs (∼30 kg) respond more quickly to CO 2 laser stimulation than larger pigs (∼60 kg). However, as for other studies using juveniles, the effect of body weight has not been analysed independently of age (Ting et al, 2010;Guesgen et al, 2011) and it is not possible to establish whether or not it was a contributing variable in any differences observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Di Giminiani et al (2013) have demonstrated that smaller pigs (∼30 kg) respond more quickly to CO 2 laser stimulation than larger pigs (∼60 kg). However, as for other studies using juveniles, the effect of body weight has not been analysed independently of age (Ting et al, 2010;Guesgen et al, 2011) and it is not possible to establish whether or not it was a contributing variable in any differences observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, as for other studies using juveniles, the effect of body weight has not been analysed independently of age (Ting et al, 2010;Guesgen et al, 2011) and it is not possible to establish whether or not it was a contributing variable in any differences observed. It is possible that both behavioural differences in younger animals and cutaneous neural density will impact upon speed of response (Di Giminiani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research into pain uses animal models extensively, including rats, mice, dogs, cats, rabbits, and to a lesser extent guinea pigs, cows, pigs, sheep, birds, hamsters, frogs and reptiles (Mogil, 2009). Much of this research aims to increase our understanding of how humans process pain, indicating that the animal and human systems are considered to be comparable for many aspects (Di Giminiani et al, 2013;Mogil, 2009). In addition to similarities in the peripheral wiring of the pain system, there are many examples showing the similarities in higher order processing of pain and other information between humans and primates, and rats.…”
Section: -Painmentioning
confidence: 99%